2020
DOI: 10.1177/0031512520952915
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Use Among High Level Swimmers Is Associated With Mental Fatigue and Slower 100- and 200- but Not 50-Meter Freestyle Racing

Abstract: Discovering any performance degradation effect of racing swimmers’ use of social media smartphone apps might lead to new training and race preparation protocols, including pre-meet smartphone avoidance. This study’s objective was to analyze the performance effects of using smartphone social media apps on the 50, 100, and 200-m freestyle among 25 high-level swimmers. Each participant performed the three race distances in two conditions: with smartphone app exposure (50-MF, 100-MF, and 200-MF) and without (50-CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Before each session, participants were instructed to attend all conditions in a well-rested state (i.e., sleep for at least eight hours and to abstain from any physical exercise and alcohol ingestion in the 48-hours before the sessions). Additionally, caffeine, nicotine, and smartphone use (e.g., social media) were to be avoided for at least three hours before the sessions (Azevedo et al., 2016; Fortes et al., 2021). A previous study showed that subjective mental fatigue recovered post-60 minutes of mental fatigue induced by 45-minutes of the Stroop task and almost recovered after 45-minutes of the AX-CPT task (Smith et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before each session, participants were instructed to attend all conditions in a well-rested state (i.e., sleep for at least eight hours and to abstain from any physical exercise and alcohol ingestion in the 48-hours before the sessions). Additionally, caffeine, nicotine, and smartphone use (e.g., social media) were to be avoided for at least three hours before the sessions (Azevedo et al., 2016; Fortes et al., 2021). A previous study showed that subjective mental fatigue recovered post-60 minutes of mental fatigue induced by 45-minutes of the Stroop task and almost recovered after 45-minutes of the AX-CPT task (Smith et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…(2019) showed that 30- and 45-minute exposure times to smartphone networking apps acutely reduced inhibition control and passing decision-making among professional soccer players. More recently, Fortes et al. (2021) also found that 30-minutes of continuous social media on smartphones induced mental fatigue in high-level swimmers (e.g., impaired Stroop task response time and increase perceived mental fatigue).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In order to understand the impact of this condition on performance, instruments which require cognitive demands through sustained attention, inhibition of response, and goal maintenance have been used, the most common instruments are computer tests the Stroop task, 7 and the AX CPT 4 . In addition, other common situations such as using smartphones before exercising can also cause this condition 12 . However, the literature normally investigates cognitive stimulation prior to exercise 12,13 , disregarding the effects of physical exercise , on mental fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other common situations such as using smartphones before exercising can also cause this condition 12 . However, the literature normally investigates cognitive stimulation prior to exercise 12,13 , disregarding the effects of physical exercise , on mental fatigue. Some studies have recently shown that physical exercise can cause mental fatigue; for example, Xu 15 performed an experimental protocol on a cycle ergometer 15 .…”
Section: Introductionmentioning
confidence: 99%